The effect of leaf-pruning on nutrient intake and in vivo digestibility of soybean stovers by sheep - Dada, S.A.O.; Akinsoyinu, A.O.; Smith, Jimmy W.; Dashiell, Kenton E. (Informa UK Limited, 2002)
Nutrients of soybean stovers (SBS) from three soybean varieties: TGx 923-2E (SBS1), TGx 1660-19F (SBS2) and TGx 1019-2EN (SBS3) whole plant (WP) and leaf-pruned stem (LPS) were compared, and these SBS (WP and LPS) were offered to West African dwarf sheep to measure voluntary dry matter (DM) intake (VDMI) and apparent crude protein (CP) and cell wall constituent digestibility coefficients. Average DM, CP, ash and cell wall phenolics concentrations inWPwere higher than in LPS by 1.53, 33.65, 1.47 and 96.15%, respectively. In contrast, average NDF, ADF, ADL, cellulose and hemicellulose concentrations of LPS were higher than in WP by 1.73, 1.87, 2.93, 1.19 and 1.44%, respectively. DailyDMintake by sheep fed SBS2 (WP; 36.2 g kg BW) was lower (P < 0.05) than other tested stovers with a similar (P > 0.05) average intake value of 41.8 kg BW0.75. Corresponding (P > 0.05) average daily CP intake by sheep fed SBS1, SBS2 and SBS3 (WP; 5.1 g kg BW0.75 was higher (P < 0.05) than the CP intake of sheep fed SBS1, SBS2 and SBS3 (LPS). Neutral detergent fibre digestibility values of 3 SBS (WP) and N-retention coefficient of 3 SBS (WP) were significantly (P < 0.05) higher than the values obtained from the 3 SBS (LPS). It is concluded that leaf-pruning has no significant beneficial effect on the feeding of soybean stovers to sheep.